2017
DOI: 10.1007/s00784-017-2067-5
|View full text |Cite
|
Sign up to set email alerts
|

Electroplated telescopic retainers with zirconia primary crowns: 3-year results from a randomized clinical trial

Abstract: Although these results encourage the use of zirconia primary crowns, more research is necessary to reduce the number of complications observed for secondary telescopic crowns, for example, failure of the veneer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…The 126 dentures reported in this study compare favorably to 60, 73, or 92 dentures in similar studies on telescopic dentures, also including 117 and 56 dentures which were retrospectively analyzed for their clinical success by Schwindling et al Our mean observation period of 45.25 ± 25.11 months is well in agreement with previous studies, some of which covered shorter (2, 7, or 3 years) and some of them longer follow‐up periods . Both this good comparability and the statistical significance of our results argue in favor of the study design, also given a gender distribution that may be considered balanced, an age structure (65.58 ± 10.47 years) consistent with similar studies and the inclusion not only of mandibular, but also of maxillary prostheses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The 126 dentures reported in this study compare favorably to 60, 73, or 92 dentures in similar studies on telescopic dentures, also including 117 and 56 dentures which were retrospectively analyzed for their clinical success by Schwindling et al Our mean observation period of 45.25 ± 25.11 months is well in agreement with previous studies, some of which covered shorter (2, 7, or 3 years) and some of them longer follow‐up periods . Both this good comparability and the statistical significance of our results argue in favor of the study design, also given a gender distribution that may be considered balanced, an age structure (65.58 ± 10.47 years) consistent with similar studies and the inclusion not only of mandibular, but also of maxillary prostheses.…”
Section: Discussionsupporting
confidence: 91%
“…Similar repair requirements have been reported in other studies . One reason for the remarkably low number of only three veneer‐ and two crack‐related repairs among our 126 dentures lies in the fabrication process, as zirconia can be processed into primary crowns featuring a wall thickness down to 0.3 mm, which minimizes the requirements for hard‐tissue reduction and leaves more space for especially stable and esthetic veneers . Few repairs were also required by the telescopes: only one primary crown and one secondary coping had to be remade, thus confirming the clinical track record of zirconia primary crowns as reported previously by Rinke et al Attention to tooth fractures under telescopic dentures, here identified as another cause of abutment loss besides endodontic problems, has been drawn previously …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…5 Kaplan-Meier survival curves of dentures in the NSRD group and Steffel classes (NSRD, not severely reduced dentition) clinical study to analyze DCP denture survival over 60 months. The number of patients participating in this study is comparable with other clinical studies assessing the longterm survival of different attachments, indicating that our results can be compared with these investigations [11,13,[24][25][26].…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have reported higher survival rates, such as 95.1% survival for dentures fixed on telescopic crowns [3]. Schwindling et al investigated different types of double crowns and found general survival rates of 96.5%, with 96.4% survival when using galvano crowns [24,25]. Ishida et al have reported 100% survival; however, they did not specify the type of double crown used [27].…”
Section: Discussionmentioning
confidence: 99%